2017
DOI: 10.1148/rg.2017160057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Syndromes Associated with Central Nervous System Tumors

Abstract: Several genetic tumor syndromes have associated central nervous system (CNS) neoplasms. The spectrum of syndromes that have intracranial tumor manifestations includes ataxia telangiectasia, Cowden syndrome, familial adenomatous polyposis, hereditary non-polyposis-related colorectal cancer, Li-Fraumeni syndrome, Gorlin syndrome, neurofibromatosis types 1 and 2, multiple endocrine neoplasia type 1, tuberous sclerosis complex, von Hippel-Lindau disease, and Turcot syndrome. Many of these disorders are inherited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…The high frequency of TERT promoter mutation occurred in SHH MBs of adult patients [40]. Genetic syndromes with germline mutations associated with MBs [41][42][43] included Gorlin syndrome (heterozygous germline pathogenic variant in PTCH1 or SUFU) [44,45], CMMR-D syndrome (biallelic deleterious germline mutations in MMR genes (MLH2, MSH2, MSH6, and PMS2)) [46], Li-Fraumeni syndrome (germline mutation of TP53) [47,48], familial adenomatous polyposis syndrome (germline APC muttaion) [4,49], and Cowden syndrome (germline mutation of PTEN) [41,50]. In our cohort series, we identified somatic mutations in BRCA2, PALB2, MSH6, PMS2, PTCH1, SUFU, TP53, APC, and PTEN from RNA-Seq data analysis.…”
Section: Finding Clues To Genetic Predispositionmentioning
confidence: 98%
“…The high frequency of TERT promoter mutation occurred in SHH MBs of adult patients [40]. Genetic syndromes with germline mutations associated with MBs [41][42][43] included Gorlin syndrome (heterozygous germline pathogenic variant in PTCH1 or SUFU) [44,45], CMMR-D syndrome (biallelic deleterious germline mutations in MMR genes (MLH2, MSH2, MSH6, and PMS2)) [46], Li-Fraumeni syndrome (germline mutation of TP53) [47,48], familial adenomatous polyposis syndrome (germline APC muttaion) [4,49], and Cowden syndrome (germline mutation of PTEN) [41,50]. In our cohort series, we identified somatic mutations in BRCA2, PALB2, MSH6, PMS2, PTCH1, SUFU, TP53, APC, and PTEN from RNA-Seq data analysis.…”
Section: Finding Clues To Genetic Predispositionmentioning
confidence: 98%
“…Five out of the 12 reported pediatric cases (41.6%) developed the second tumor 6 to 21 years following radiation therapy to the first tumor. Radiation therapy was focal in 2 cases, craniospinal in 2 cases, and whole brain in 1 case) [2,4,10,12,15,21,25,29]. Our first case did not have any genetic predisposition syndromes, the second case was never tested.…”
Section: Discussionmentioning
confidence: 70%
“…Histopathologically, they usually constituted of meningiomas and astrocytomas and are more common in patients with known underlying genetic syndromes or after radiation therapy for previous brain tumors [1,[5][6][7][8][9]11,22]. We performed a comprehensive literature review and identified a total of twelve pediatric cases with synchronous/ metachronous brain tumors [2,4,10,12,15,21,25,26,27,29]. In this report, we describe two rare cases of children with multiple brain tumors exhibiting different histologic subtypes and occurring simultaneously in the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations